Development English Skills; Listening and Speaking for Member of Sub-district Administrative Organization Nong Rua Sub-district, Phraikhla Sub-district, Krabuang Sub-district, Chumphonburi, Surin Province - Srakaew, Phra Narong Thanawuttho (Wishing Journal Review, 2022)
The research entitled “Development English Skills; Listening and Speaking for Member of Sub-district Administrative Organization Nong Rua Sub-district, Phraikhla Sub-district, Krabuang Sub-district, Chumphonburi, Surin Province”. It was Mixed Research Method according to research regulations as follow, 1) Survey Research, 2) Quality Research. The objectives, namely; 1) To study skill for listening and speaking English. 2) To study attitude problems skill for listening and speaking English. 3) To study suggestions as concern with “Development English Skills; Listening and Speaking for Member of Sub-district Administrative Organization Nong Rua Sub-district, Phraikhla Sub-district, Krabuang Sub-district, Chumphonburi, Surin Province”. The instruments used in the study was semi-structured interview and questionnaires about the opinions of Administrative Organization people. There were analyzed by Mean Standard Deviation then interpreted according to sequence of 5 benchmarks the most more medium less and least as defended. The result of research was found as follows; The revel of opinion for “Development English Skills; Listening and Speaking for Member of Sub-district Administrative Organization Nong Rua Sub-district, Phraikhla Sub-district, Krabuang Sub-district, Chumphonburi, Surin Province” by overall had more revel as ( =4.24, S.D. = 0.188). Then when consider by each part found that the most revel was activities skill for speaking as ( =4.31, S.D. = 0.357) next for more revel was activities skill for listening as ( = 4.30, S.D. = 0.57) then next was activities skill for media had more revel as ( = 4.23, S.D. = 0.323). The least revel opinion was skill for process learning had more as ( = 4.12, S.D. = 0.351). Acknowledgement from research “Development English Skills; Listening and Speaking for Member of Sub-district Administrative Organization Nong Rua Sub-district, Phraikhla Sub-district, Krabuang Sub-district, Chumphonburi, Surin Province” by overall for 4 skills had more revel by summarize as follow; 1) Listening skill, it had less for investment but got more profited so we must do by attendance for clear matter. 2) Reading or Thinking skill, it was known message and consider them. Therefore, we must guest and keep for directly matter. 3) Speaking skill, it was shown matter words translated words for clear and the all the clearest. 4) Writing skill, it was the latest part for keeping matters as communicate for what, where, when, why, for still and lasting.